Quantitative Proteomic Analysis of Duck Embryo Fibroblasts Infected With Novel Duck Reovirus - Yang, Yudong; Li, Lin; Liu, Xingpo; Jiang, Meijie; Zhao, Jun; Li, Xuesong; Zhao, Cui; Yi, Hui; Liu, Sidang; Li, Ning (Frontiers in Veterinary Science, 2020)
The novel duck reovirus (NDRV) can cause hemorrhage and necrosis on the spleen of Pekin ducks, this disease has resulted in great economic losses to the duck industry. However, the molecular pathogenesis of NDRV remains poorly understood. In the current study, the quantitative proteomic analysis of NDRV-infected duck embryo fibroblasts was performed to explore the cellular protein changes in response to viral infection through iTRAQ coupled with the LC–MS/MS method. A total of 6,137 proteins were obtained in cell samples at 24 hours post infection. Of these, 179 differentially expressed proteins (DEPs) were identified (cutoff set to 1.5-fold change), including 89 upregulated and 90 downregulated proteins. Bioinformatic analysis showed that DEPs can be divided into the cellular component, molecular function, and biological process, they were mainly involved in the signal transduction, infectious diseases, cell growth and death, and the immune system. The subcellular localization of most proteins was cytoplasm. Importantly, the expression of signal transducer and activator of transcription 1 (STAT1) and various interferon-stimulated genes (ISGs) were upregulated after NDRV infection. The mRNA transcripts of some ISGs were consistent with proteomic data, showing an increased trend. Results of our study suggested that NDRV infection can elicit the strong expression changes of cellular proteins, and activate the expression of ISGs from the point of quantitative proteomic analysis. The study provides a new insight into the understanding of NDRV pathogenesis.